Neurobehavioral assessment and brain acetylcholinesterase levels in rats subchronically exposed to fipronil - Barretto, M. L. M.; Horta, D. F. [UNESP]; Anselmo, F. [UNESP]; Godinho, A. F. [UNESP]; Oliveira, A. A. F. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2020)
Fipronil is a selective-toxicity insecticide widely used in agriculture and veterinary medicine. However, there are reports of neurotoxic effects of this substance, causing damages to vertebrates. We evaluated the locomotor activity, motor coordination and the activity of brain acetylcholinesterase in rats exposed to fipronil. Adult male Wistar rats (n=15) received fipronil at a dose of 30mg/kg orally for 15 days; the Control group (n=15) was treated with oral solution in the same period. On the 16th day of experimentation, the animals were submitted to the open field arena test and hole-board test. On the 17th day, they were anesthetized and euthanized, and organs were collected, and subsequently brain AChE was evaluated. Exposure to fipronil yielded no significant changes on motor coordination and locomotor activity but caused significant inhibition of brain acetylcholinesterase activity. These findings suggest that fipronil may cause short-term neurotoxic effects, which may be exacerbated if exposure is prolonged.
Keywords: pesticides; phenylpyralozes; neurotoxicity; open field test; hole-board test